2021
DOI: 10.1111/tbed.14020
|View full text |Cite
|
Sign up to set email alerts
|

Can improving animal health and biosecurity knowledge of para‐veterinarians in Cambodia assist in addressing challenges in smallholder livestock farming?

Abstract: Para‐veterinarians are crucial in providing front‐line veterinary care and advice to smallholder farmers in countries with under‐resourced national veterinary services. Many of these individuals undergo basic training with minimal monitoring and evaluation of performance and knowledge levels. To identify the knowledge, attitudes and practices of Cambodian para‐veterinarians a cross‐sectional survey (n = 80) of Village Animal Health Workers (VAHWs) was conducted during August 2018 in the provinces of Tbong Khmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The conclusion from the 2013 study confirmed that it is worthwhile for farmers to participate in the full-fee bi-annual FMD vaccination programme if there are average annual outbreaks with a morbidity rate of approximately 30% and two major outbreaks with morbidity rate above 50% in the ensuing 5 years. This is consistent with conclusions from the 2015 survey that also suggested that improved training of VAHWs could ensure they remain important in supporting the under-resourced national veterinary services(MacPhillamy et al, 2022). In that study, binomial logistic regression modelling found the length of employment (p = .003), reporting of pig diseases (p = .007), recommending the quarantine of newly purchased animals (p = .008), treatment of cases of HS with antibiotics (p = .032) and the washing of footwear with water when entering or leaving a farm (p = .008), were all positively associated with a higher (≥92%) animal health and biosecurity knowledge score(MacPhillamy et al, 2022).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The conclusion from the 2013 study confirmed that it is worthwhile for farmers to participate in the full-fee bi-annual FMD vaccination programme if there are average annual outbreaks with a morbidity rate of approximately 30% and two major outbreaks with morbidity rate above 50% in the ensuing 5 years. This is consistent with conclusions from the 2015 survey that also suggested that improved training of VAHWs could ensure they remain important in supporting the under-resourced national veterinary services(MacPhillamy et al, 2022). In that study, binomial logistic regression modelling found the length of employment (p = .003), reporting of pig diseases (p = .007), recommending the quarantine of newly purchased animals (p = .008), treatment of cases of HS with antibiotics (p = .032) and the washing of footwear with water when entering or leaving a farm (p = .008), were all positively associated with a higher (≥92%) animal health and biosecurity knowledge score(MacPhillamy et al, 2022).…”
supporting
confidence: 87%
“…This suggests that more effective VAHWs could receive more calls and generate more income from providing their services both within and between villages during the disease outbreaks. However, it is noted that frequent VAHWs travel and contact with different animals is a high-risk activity for disease transmission, Increasing information is emerging on the importance of FMD vaccination and biosecurity in Cambodia, and the importance of progressing this issue more effectively with VAHWs and smallholder farmers is necessary, as this may contribute significantly to the improvement of the vaccination uptake by rural communities and assist the development of more effective disease control strategies in the country (MacPhillamy et al, 2019(MacPhillamy et al, , 2022Stratton et al, 2015;Young, Suon, & Andrews, et al, 2013, 2016, 2017. The veterinary authorities at the central and provincial levels need to focus their attention on several aspects of the vaccine supply chain, including the provision of sufficient doses of high-quality vaccines from reliable vaccine suppliers that are matched to currently circulating FMD serotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge, attitudes, and practices of antibiotic use among technicians in Timor-Leste should be investigated since this is currently unknown and will help identify how technicians can be better equipped to promote prudent use practices among farmers ( 26 , 55 ). Such a study can also identify any drivers of inappropriate usage among these animal health professionals that need to be circumvented, given drivers such as financial incentives have been reported by para-veterinarians in another Southeast Asian LMIC ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the important role that paraprofessionals can play in disease prevention and even eradication (85)(86)(87). A second component for paraprofessionals to play a key role in disease prevention and eradication is revived and standardized training of paraprofessionals, something that is also emphasized in other studies (88,89). Smallholders also need to have strategies to distinguish between the relative qualifications of the various veterinary actors providing services (90).…”
Section: Discussionmentioning
confidence: 99%